Notions of India in A.J. Cronin’s Hatter’s Castle - Wirth, Robert (Imperial Middlebrow: Cross-colonial encounters and expressions of power in middlebrow literature and culture, 1890-1940)

Putting the ‘Great’ Back Into Great Britain - Wirth, Robert (Britain in Europe / Europe in Britain)

Cultural and Textual Appropriation in Alan Bissett's Boyracers (Litteraria Pragensia: Studies in Literature and Culture)

Reaktivität verstehen, ohne die Katalysatorstruktur zu kennen - Paradies, Jan (Nachrichten aus der Chemie)
Abstract Manche boranbasierten frustrierten Lewis‐Paare spalten Wasserstoff – wie, war bislang unklar. Um Struktur und Reaktivität in Beziehung zu setzen, werden quantenchemische Untersuchungen und NMR‐Experimente kombiniert. Sind pK a ‐Werte der Lewis‐Base bekannt, lässt sich damit Reaktivität vorhersagen.

Organische Chemie 2016 - Straub, Bernd F.; Andexer, Jennifer; Arenz, Christoph; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ditrich, Klaus; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kordes, Markus; Krueger, Anke; et al. (Nachrichten aus der Chemie)

Chiral Borane-Based Lewis Acids for Metal Free Hydrogenations - Paradies, Jan (Topics in Organometallic Chemistry)

Franz-Josef Arlinghaus (Ed.), Forms of Individuality and Literacy in the Medieval and Early Modern Periods, Turnhout, Brepols Publishers, 2015 - Mersch, Katharina Ulrike (Historische Zeitschrift)

Businessmen and Local Elites in the Lycos Valley - Droß-Krüpe, Kerstin (Sinews of Empire: Networks and Regional Interaction in the Roman Near East and Beyond)

Great Women on Stage. The Reception of Women Monarchs from Antiquity in Baroque Opera - Droß-Krüpe, Kerstin (Great Women on Stage. The Reception of Women Monarchs from Antiquity in Baroque Opera)

Ars polymita, ars plumaria: the Weaving Terminology of Taqueté and Tapestry - Droß-Krüpe, Kerstin; Wild, John Peter (Textile Terminologies from the Orient to the Mediterranean and Europe 1000 BC - AD 1000)

χιτών - δαλματική - μαφόρτης - σύνθεσις. Common and Uncommon Garment Terms in Roman Egypt - Droß-Krüpe, Kerstin (Textile Terminologies from the Orient to the Mediterranean and Europe 1000 BC - AD 1000)

Die Pacht von gewerblichen Räumen im römischen Ägypten - Prinzipale und Agenten? - Droß-Krüpe, Kerstin (MBAH)

Great Women on Stage. The Reception of Women Monarchs from Antiquity in Baroque Opera

Capital Charge Rates, Investment Incentives and Taxation - Bauer, Thomas; Kourouxous, Thomas (European Accounting Review)
This paper studies the impact of personal and corporate income taxation on capital charge rates in a delegation setting with a risk-averse manager. If the investment level influences the riskiness of the investment project, the capital charge rate deviates from the firm's cost of capital and depends crucially on the manager's personal income tax rate. Contradicting conventional wisdom, we find that a higher personal income tax rate induces higher investment expenditures and, surprisingly, increases the capital charge rate. The countervailing effect that a higher capital charge rate induces higher and not lower investment expenditures persists for pre-tax and after-tax performance measures as well as when the tax deductibility of managerial compensation is limited. Corporate income tax causes a similar effect only in the case of limited tax deductibility of compensation. Our insights remain valid regardless of the financing structure and the risk attitude of the investors.

Forschen lehren und forschen lernen im Werkstattmodus. Konzepte, Erfahrungen und Befunde aus dem Wissenschaftsbetrieb - Thünemann, Silvia; Freitag, Christine (Lernwerkstattarbeit als Prinzip. Möglichkeiten für Lehre und Forschung)

P 13 Congruency between speech-related areas investigated by fMRI and three rTMS protocols with different frequencies - Nettekoven, C.; Reck, N.; Pieczewski, J.; Neuschmelting, V.; Thiele, Kristina; Grefkes, C.; Goldbrunner, R.; Lucas, C. Weiß (Clinical Neurophysiology)

P228 Better tolerability and lower mean intensities favour higher-frequent stimulation as compared to 10 Hz online-rTMS for language mapping: A test–retest reliability study in healthy volunteers - Pieczewski, J.; Nettekoven, C.; Neuschmelting, V.; Jonas, Kristina; Grefkes, C.; Goldbrunner, R.; Weiss Lucas, C. (Clinical Neurophysiology)

P 14 Motor component of speech errors in rTMS language mapping - Lucas, C. Weiß; Pieczewski, J.; Nettekoven, C.; Neuschmelting, V.; Jonas, Kristina; Goldbrunner, R.; Grefkes, C. (Clinical Neurophysiology)

P 12 Integrating nTMS motor mapping of the M1 tongue area into diffusion tractography to reconstruct motor-speech pathways - Pieczewski, J.; Nettekoven, C.; Neuschmelting, V.; Jonas, Kristina; Hoevels, M.; Reck, N.; Tittgemeyer, M.; Grefkes, C.; Goldbrunner, R.; Lucas, C. Weiss (Clinical Neurophysiology)

Überlegungen zur Anbahnung nähesprachlicher Kommunikationsfähigkeit im Spanischunterricht - Bürgel, Christoph; Leitzke-Ungerer, Eva; Polzin-Haumann, Claudia (Varietäten des Spanischen im Fremdsprachenunterricht. Ihre Rolle in Schule, Hochschule, Lehrerbildung und Sprachzertifikaten)